2013
DOI: 10.1167/iovs.13-12650
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Macrophage Phenotype in Rejected Corneal Allografts

Abstract: Increased numbers of macrophages in rejected corneal allografts implicate that these cells might contribute to the immunopathogenesis of corneal graft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…Notably, M1 macrophages are inflammatory cells, whereas M2 macrophage resolve inflammation and thus play critical roles in tissue remodeling and wound healing. Previous reports of corneal studies indicate that M2 macrophages function in the wound repair process in this tissue [21,26]. Therefore, our observation that H 2 treatment promotes M2 macrophage expression suggests another potential clinical application of this therapy.…”
Section: Discussionsupporting
confidence: 60%
“…Notably, M1 macrophages are inflammatory cells, whereas M2 macrophage resolve inflammation and thus play critical roles in tissue remodeling and wound healing. Previous reports of corneal studies indicate that M2 macrophages function in the wound repair process in this tissue [21,26]. Therefore, our observation that H 2 treatment promotes M2 macrophage expression suggests another potential clinical application of this therapy.…”
Section: Discussionsupporting
confidence: 60%
“…While M1 macrophages mediate injury, M2 macrophages are generally implicated in injury resolution and tissue remodeling, and therefore, they may promote allograft damage repair; though currently, their role in acute injury remains speculative. Histological studies of murine corneal allografts exhibiting acute rejection revealed the presence of M1 macrophages secreting proinflammatory mediators, while M2 macrophages were detected in the animals that did not reject the transplants [64]. An M1-dominant response was also observed in a rat model of acute renal AMR and in clinical biopsy samples of acutely rejecting kidney allograft recipients [65].…”
Section: Macrophages In Acute Allograft Rejectionmentioning
confidence: 99%
“…Although mechanisms and molecules associated with macrophage plasticity and polarized activation have been studied in tumors, diseases of the central nervous system, or tissue transplantation (Biswas and Mantovani 2010; Oh et al 2013; Sica 2010; Shechter and Schwartz 2013), there have been few studies on differentiation and distribution of macrophages in dry eye associated inflammation. Thus, we investigated the phenotype of macrophages in ocular surface tissues of experimental dry eye in mice.…”
Section: Introductionmentioning
confidence: 99%